Isothermal Crystallization of Palm Oil‐Based Fats with and without the Addition of Essential Oils. (18th June 2020) - Chikhoune, Anis; Shashkov, Mikhail; Piligaev, Aleksandr Vasilyevich; Lee, Juhee; Boudjellal, Abdelghani; Martini, Silvana
Abstract: The objective of study was to evaluate the crystallization behavior of palm oil‐based fats processed with and without the addition of essential oils (5% w/w) obtained from the flowers (EsOF) and stems (EsOS) of Pituranthos scoparius . Palm oil (PO) and a mixture of PO, soybean oil, and sunflower oil (Mix) were tested. The addition of the essential oils did not change the melting points of the fats but affected their crystallization behavior. A delay in crystallization was observed, evidenced by lower crystallization rates, and lower solid fat contents. This delay was comparable in the samples crystallized with EsOF and EsOS for the PO samples but EsOF was more efficient at delaying crystallization in the Mix sample. EsOF generated a less organized crystalline network in both samples (lower enthalpy values) while EsOS generated a more organized crystalline network (high enthalpy values) when used in the Mix sample. The addition of EsO also affected the crystal microstructure in some cases. While a slight increase in crystal size was observed for some PO samples crystallized with EsOF, no change or a decrease in crystal size was observed for the samples crystallized with EsOS. A slight decrease in crystal size was observed for Mix samples crystallized with EsOF while no effect was observed for these samples crystallized with EsOS. Results from this study show that these essential oils can be used as natural additives to modify the crystallization of fats for food applications and therefore widen their functional properties.